The effect of alcohol on the performance of lipase-immobilized enzymatic membrane reactor for esterification of (R,S)-ketoprofen - Ong, Ai Lien; Chuan Fu, Kian; Harun @ Kamaruddin, Azlina; Bhatia, Subhash (2006)
The effect of alcohols on the performance of lipase-immobilized enzymatic membrane reactor (EMR) for enantioselective esterification of (R,S)-ketoprofen has been studied. In this work, mixed solvent medium was used and the (R)-ketoprofen was reacted with the different alcohols in the presence of immobilized lipase B from Candida antartica, leaving the target product (S)-ketoprofen in its unreacted form. The alcohols involved in the reactions were ethanol, butanol, heptanol and 2-ethoxyethanol. The chain length of alcohol was found to significantly affect the performance of the esterification in EMR. Through the alcohols screening, the esterification reaction using ethanol in EMR showed higher initial rate, conversion, enzyme enantioselectivity, enantiomeric excess of substrate (ees) and enantiomeric excess of product (eep). However the results with butanol showed less inhibition effect on a wider range of temperature